PUBLIC PRIVATE PARTNERSHIPS IN ROMANIA VERSUS ALBANIA: THE CHALLENGES TO IMPROVE LEGISLATION FOR ATTRACTING MORE FINANCIAL RESOURCES - Lizeta Aneziane; Dalina Dumitrescu (European Scientific Journal, ESJ, 2014)
Having in mind the current international economic context and the economic crisis without precedent, implementing public-private partnerships represents an essential tool for developing the emerging markets and for finalizing large scale infrastructure projects, with a great positive impact on the long term. Major focus is being put on private-public partnerships during the last years, as the world economy is growing and also turbulent times were passed through starting with 2008, when the international financial crisis started. Various countries around the world in general, and around Europe, in particular, apply different type of private – public partnerships: even though the partnership applied is a concession or a institutional PPP, the expected result is the same: the goal of attracting money and finishing important projects, of national interest should be achieved either way. Still, some countries manage to finish successful PPPs, other pass through permanent legislative changes and no final results are encountered. What is the path towards success? Trying to answer the above question, the elements that make the difference between applying different kind of partnerships, following different legislation are analyzed. Albanian and Romanian legislation applied during 2012 are discussed through comparison, starting with the EBRB classification and ranking among less compliant towards most compliant legislations. Improvement solutions are proposed for both countries in the attempt to attract as many financial resources as possible.